Using mass-media communications to increase population usage of Australia's Get Healthy Information and Coaching Service® - O'Hara Blythe J; Bauman Adrian E; Phongsavan Philayrath (BMC, 2012)
Abstract Background Global obesity prevalence is increasing and population health programs are required to support changes to modifiable lifestyle risk factors. Such interventions benefit from mass-communications to promote their use. The Get Healthy Information and Coaching Service ® (GHS) utilised mass-reach media advertising to recruit participants to an Australian state-wide program. Methods A stand alone population survey collected awareness, knowledge and behavioural variables before the first advertising phase, (n = 1,544; August -September 2010), during (n = 1,500; February - March 2011) and after the advertising period (n = 1,500; June-July 2011). GHS usage data (n = 6,375) was collated during July 2010 - June 2011. Results The results showed that television-lead mass-media significantly increased unprompted awareness (0% to 31.8%, p < 0.001); prompted awareness (2.5% to 23.7%, p < 0.001); and understanding (10.2% to 32.2%, p < 0.001). Mass-media (television, print and mail out information) was more often cited as the source of referral by males, those aged 18 - 49 years, employed, and from the lowest socio-economic groups. During the weeks when mass-media advertising was present, 4 and 2.5 times more information and coaching participants respectively registered than when there was no advertising present. Participants who cited television and print were less likely to enrol in GHS coaching, but this was not the case for mail out information and secondary referral sources. Conclusions GHS mass-communications campaigns are effective at increasing awareness and usage of the GHS, especially among hard-to-reach population groups. Television advertising provides universal reach, but should be supplemented by health professional referrals and targeted mail-out information to recruit participants to the intensive GHS coaching program.